Android based vehicle tracking system - Safdar, Saima; Zeb, Anwar; Khan, Ajmal; Kaleem, Zeeshan (EAI Endorsed Transactions on Energy Web, 2018)
In this paper, an efficient vehicle tracking system is proposed that is used to track the location of any equipped vehicle with the help of an android application. The SIM808 module is used which incorporates GPS and GSM modules. The GPS module is used to get vehicle’s location coordinates. These coordinates are sent to the Smartphone with the help of a GSM module. On a Smartphone, an android based application is developed to plot the location of a vehicle on a Google map. The application also has the capability to keep the previous route history of the vehicle. The proposed system is implemented and tested in a practical environment. Experimental results have proved that the proposed tracking system is accurate and feasible for the vehicle owners.